Where to Create Jobs : Cities or Towns? - Christiaensen, Luc (World Bank, Washington, DC, 2017)
Should public investment be targeted to big cities or to small towns, if the objective is to minimize national poverty? To answer this policy question the authors extend the basic Todaro-type model of rural-urban migration to the case of migration from rural areas to two potential destinations, secondary town and big city. The authors first derive labor income, migration cost and poverty line conditions under which a poverty gradient from rural to town to city will exist as an equilibrium phenomenon. The authors then develop sufficient statistics for the policy decisions based on these income parameters. The empirical remit of the model is illustrated with long running panel data from Kagera, Tanzania. Further, we show that the structure of the sufficient statistics is maintained in the case where the model is generalized to introduce heterogeneous workers and jobs.